Use of Nanofluids in Solar PV/Thermal Systems - Asmaa Ahmed; Hasan Baig; Senthilarasu Sundaram; Tapas K. Mallick (International Journal of Photoenergy)
The continuous growth in the energy demand across the globe due to the booming population, in addition to the harmful effects of the fossil fuels on the environment, has made it essential to harness renewable energy via different technologies and convert it to electricity. The potential of solar energy still remains untapped although it has several advantages particularly that it is a clean source to generate both electricity and heat. Concentrating sunlight is an effective way to generate higher throughput per unit area of the absorber material used. The heat extraction mechanisms and the fluids used in solar thermal systems are key towards unlocking higher efficiencies of solar thermal systems. Nanofluids can play a crucial role in the development of these technologies. This review is aimed at presenting the recent studies dealing with cooling the photovoltaic thermal (PVT), concentrated photovoltaic thermal (CPVT), and other solar systems using nanofluids. In addition, the article considers the definition of nanofluids, nanoparticle types, nanofluid preparation methods, and thermophysical properties of the most common nanoparticles and base fluids. Moreover, the major factors which affect the nanofluid’s thermal conductivity according to the literature will be reviewed.